2016
DOI: 10.3109/03009742.2016.1152399
|View full text |Cite
|
Sign up to set email alerts
|

Association between bone turnover markers, clinical variables, spinal syndesmophytes and bone mineral density in Mexican patients with ankylosing spondylitis

Abstract: We observed an increase in OC levels in AS patients with syndesmophytes. BTM levels were associated with the severity of spinal damage. Future longitudinal studies should evaluate whether these BTMs should be included as tools to determine the prognosis and progression of spinal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Bone turnover markers (BTM) may also reflect the processes leading to excessive bone formation in axSpA: serum C-terminal telopeptide fragments of type I collagen (sCTX), a bone resorption marker, as well as bone formation markers procollagen type I N-terminal peptide (PINP) and osteocalcin (OC) were elevated in AS patients with bridging syndesmophytes [2,19]. Another marker of bone formation, bone-specific alkaline phosphatase (BALP), which is increased during TNFi treatment, may be associated with a simultaneous increase of bone mineral density (BMD) [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Bone turnover markers (BTM) may also reflect the processes leading to excessive bone formation in axSpA: serum C-terminal telopeptide fragments of type I collagen (sCTX), a bone resorption marker, as well as bone formation markers procollagen type I N-terminal peptide (PINP) and osteocalcin (OC) were elevated in AS patients with bridging syndesmophytes [2,19]. Another marker of bone formation, bone-specific alkaline phosphatase (BALP), which is increased during TNFi treatment, may be associated with a simultaneous increase of bone mineral density (BMD) [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The systemic measurement may therefore disturb the serological measurement in terms of bone formation. In contrast to the observed pathological changes, most studies found no difference in serum levels of bone formation markers, like osteocalcin, PINP and bone specific ALP, in patients with AS compared with their control groups [226,[229][230][231][232]. However, increased osteocalcin [230] and PINP levels [233] in AS patients, if present, correlate well with the progression of radiographic syndesmophytes and ankylosis ( Table 5).…”
Section: Tissue Turnover Markers In Ankylosing Spondylitismentioning
confidence: 97%
“…CTX-I is elevated in the serum [230] and urine [229] of AS patients, and is associated with radiographic progression [233]. However, serum CTX-I levels remain unaltered after anti-TNFα treatment in these patients [234].…”
Section: Tissue Turnover Markers In Ankylosing Spondylitismentioning
confidence: 99%
“…[ 1 , 2 ] With rapid progression, AS generally attacks young people, and exhibits poor prognosis when treatments are delayed or inappropriate. [ 3 ] In AS patients, the most common clinical symptom is back pain which is featured by morning stiffness and alleviation after exercises. [ 4 , 5 ] The sign of this disease is acute and chronic inflammations at sacroiliac joint and at the points of tendons and ligaments attaching to the bone.…”
Section: Introductionmentioning
confidence: 99%